Doing Christian ethics : context and perspective - Mabry, Hunter P.; Serampore College. Board of Theological Education (Bangalore : Board of Theological Education of the Senate of Serampore College, 1996)
Papers presented at a workshop held at the United Theological College, Bangalore, 1-12 June 1993 under the auspices of the Board of Theological Education of the Senate of Serampore College.
Includes bibliographical references.
Keywords: Christian ethics -- Congresses; Theology -- Congresses; Social ethics -- Congresses